2018
DOI: 10.1111/ceo.13333
|View full text |Cite
|
Sign up to set email alerts
|

Topical axitinib is a potent inhibitor of corneal neovascularization

Abstract: Topical administration of the three axitinib concentrations inhibited CNV in rabbits, blocking both vascular endothelial growth factor and platelet-derived growth factor pathways. Axitinib at 0.5 mg/mL induced profound inhibition of corneal angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Topical application of axitinib showed a dose-dependent inhibition of CoNV area and corneal stroma vascularization in a rabbit suture-induced CoNV model. Sunitinib tested using the same methodology showed similar reduction in CoNV with no significant difference in level of CoNV compared to axitinib [43].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 83%
“…Topical application of axitinib showed a dose-dependent inhibition of CoNV area and corneal stroma vascularization in a rabbit suture-induced CoNV model. Sunitinib tested using the same methodology showed similar reduction in CoNV with no significant difference in level of CoNV compared to axitinib [43].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 83%
“…The insignificant effect of axitinib on corneal VEGFR3 may be the result of this attribution. Riquelme et al also demonstrated topical administration of different axitinib concentrations inhibited CNV by preventing both VEGF and platelet-derived growth factor pathways 26 . It was indicated that not only the topical administration, oral use of axitinib also prevented laser-induced choroidal neovascularization 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Most studies on TKIs used to treat CNV have focused on multi-target TKIs that target VEGFR-1/3 and PDGF as well as VEGFR-2 [14,24,25,26,27,28]. Sunitinib had about three times more efficacy than bevacizumab in an animal study, but side-effects, including iris pigmentation, were also reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…There has only been one study about the effects of rivoceranib on CNV [23]. Additionally, several studies on the inhibition of tyrosine kinase pathway for CNV have focused on multi-targeted TKIs [14,24,25,26,27,28]. In this study, we compared the efficacy of topical rivoceranib to that of topical bevacizumab in the murine model of CNV.…”
Section: Introductionmentioning
confidence: 99%